Perancangan Sistem Aplikasi Sistem Stock Opname Bahan Baku Pembuatan Daging Burger Menggunakan Metode Min-Max Stock - Utami, Fidya Imanda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
UD or Trading Business is a trading business that operates in the field of making burger meat, ranging from chicken burgers to beef burgers. For trading business actors, the problem being faced in business is the supply of raw material stock, starting from inventories, stock, and repurchase if the required raw materials have run out or are lacking and also trading businesses often experience surpluses and shortages of raw materials, due to Raw material that rots easily and expires means that owners have to be more careful in making stock so that there is no loss if there is a shortage or excess of the materials they have purchased. For stock taking, this business owner still uses the manual method, namely by weighing the remaining ingredients for making burger meat which are used to make burger meat mixture, so it takes a long time to get less effective results and errors often occur in data collection. So you will make mistakes in calculating the remaining materials which will cause losses to the business. The Min-Max method is a method used to determine the maximum and minimum inventory amounts to avoid shortages and excesses. So this research aims to find out that trading businesses have carried out stock taking of materials appropriately and in a controlled manner. And create an information system for implementing applications so that it can help make inputting raw materials easier and calculating in implementing the Min-Max Stock method.